CONSEQUENCES OF DISCIPLINARY PUNISHMENT FOR PRISONERS: A CRIMINOLOGICAL LABELING PERSPECTIVE - Prastiyo, Ricky Dwi; Rahayu, Mulyani (Universitas Nusa Cendana, 2025)
This study aims to examine the consequences of disciplinary punishment for inmates from the perspective of labeling criminology, with a focus on the Pati Class IIB Correctional Institution. Disciplinary punishment in correctional institutions aims to enforce order, but it is inseparable from the labeling process and social intervention that has various consequences. This study uses qualitative methods and finds two classifications of consequences : negative and positive. Negative labeling can lead to loss of social opportunities, discrimination, isolation, and an increased risk of repeat offenders. Conversely, with support such as mentorship or rehabilitation, labeling can motivate individuals to change. The suggestion proposed is a review of disciplinary punishment rules with a focus on the balance between justice and rehabilitation, in order to minimize the negative impact on prisoners. Keywords : Consequensces; Labelling; Disciplinary Punishment